The Development of Work Environment at the National University Hospital of Iceland: Job Burnout, Job Satisfaction and Quality of Care - Knútsdóttir, Jana Katrín; Gunnarsdóttir, Sigrún; Kristinsson, Kári (Tímarit um viðskipti og efnahagsmál, 2019)
General dicussion about Icelandic health care has recently focused on the situation on Landspitali but studies about the problem are limited. Nurses form the largest health care profession and recent studies indicate their significance regarding quality of care and patient safety. Previous studies show increasing nursing work demand and signs of burnout. The objective of this study was to examine attitudes of nurses and midwives towards work environment, job satisfaction, signs of burnout and quality of care. An online survey was conducted among all clinical nurses and midwifes at Landspítali in November 2015. Data was compared to previous study with same instrument, in same setting using same method in recruiting particpants and analysing data. Key findings show that symptoms of burnout are more common and more serious, nurses and midwifes estimate the staffing as not adequate, the proportion of participants planning to leave within the 12 months has doubled and attitudes towards quality of care is similar. Same influential factors for burnout where identified; staffing, managerial support at the unit level and communication. The study is a contribution to knowledge and to the discussion about the health care services and provides staff, management and government an insight into the working environment at Landspítali og potential ways forward. Undanfarið hefur umræða um heilbrigðismál hér á landi beinst að aðstæðum og álagi innan Landspítala háskólasjúkrahússins en fræðilegar rannsóknir um vandann eru fáar. Hjúkrunarfræðingar eru stærsta starfsstétt heilbrigðisþjónustunnar og erlendar rannsóknir varpa ljósi á mikilvægi þeirra varðandi gæði þjónustu, öryggi sjúklinga og dánartíðni. Einnig sýna rannsóknir að vinnuálag hjúkrunarfræðinga er að aukast og einkenni kulnunar í starfi að verða algengari. Viðfangsefni rannsóknarinnar var að kanna hvernig hjúkrunarfræðingar og ljósmæður á Landspítala meta starfsumhverfi sitt, starfsánægju og einkenni kulnunar í starfi og gæði þjónustu á Landspítala. Gerð var rafræn ...